To the Euphrates and beyond
1 online resource (352 pages)
Keywords: This book contains papers that reflect the wide-ranging interests of the Dutch archaeologist Maurits van Loon--prehistory, art history, and ancient history. It is a mine of useful information and synthesis for archaeologists working in the region of northern Syria.